Prevalência de enteroparasitos e sua relação com o saneamento básico, em crianças em idade escolar antes e após intervenções educativas e farmacológica em Maceió/Alagoas - Agra, Thayse Pereira (2014)
Intestinal parasites are a problem of great public health importance. Both in rural areas as in urban areas, they are widespread due to poor sanitation and irrigation water is one of the major intestinal diseases transmission vehicles. We evaluated the prevalence of intestinal parasites in children aged 7 to 11, from a public school in Maceio, through parasitological examination of Lutz, popularly known as HPJ in two steps (with and without drug treatment) investigating whether there influence of sanitation and socioeconomic and environmental conditions. After preventive education and adequate pharmacological treatment, repeated parasitology and the physical analysis, chemical (titration of complexation and Argentometric - Alfakit/Ecokit) and microbial by the Technical Multiple tubes of water. It was the prevalence of Giardia lamblia and Ascaris lumbricoides in 59.25% of the positive samples. After preventive education and adequate pharmacological treatment the prevalence of intestinal parasites was statistically significant (p <0.05), being effective in reducing the degree of parasitism in the period. The water distributed for consumption at the Municipal School Rui Palmeira is not within the potability standards required by Brazilian law. The concentration of residual chlorine and the presence of fecal coliform leaves unsuitable for consumption. The study showed that not enough only minimum conditions of sanitation and public policy of urban and housing planning must also be encouraged educational practices of tutoring to raise awareness of the need to acquire the knowledge to prevent parasites.